Co-exposure of sequential extreme weather and non-biodegradable/biodegradable microplastics (NBMPs/BMPs) on soil bacterial communities and the extracellular polymeric substances (EPS)-extracellular enzyme interaction mechanisms - Xinyu Yang; Yulian Ma; Xin Wang; Yue Sun; Qianzhi Zeng; Yunhong Pu; Bowen Yang; Yaxuan Wu; Xinran Su; Linna Shi; Shuang Li; Wenzhuo Sui; et al. (Journal of Environmental Chemical Engineering, 2026)

DOM-mediated interaction of DOM-enzyme-pollutants affected the toxicity of combined aged tire wear particles (aged-TWPs) and polyfluoroalkyl substances (PFASs) in soil under successive extreme weather stress - Xin Wang; Yulian Ma; Xinyu Yang; Yue Sun; Wenzhuo Sui; Yunhong Pu; Qianzhi Zeng; Yaxuan Wu; Bowen Yang; Xinran Su; Shuang Li; Linna Shi; et al. (Journal of Environmental Management, 2026)

Effects of Perfluoroheptanoic Acid (PFHpA) on Bacterial Community, Elemental Cycling and ARGs Transmission in Sediment - Shengnan Shi; Xinran Su; Linna Shi; Shuang Li; Yunhong Pu; Qianzhi Zeng; Bowen Yang; Yaxuan Wu; Yue Sun; Yulian Ma; Xinyu Yang; Xin Wang; et al. (Water, Air, & Soil Pollution, 2026)

Study on high-content screening-based allelopathic inhibition by Macleaya cordata extracts on Microcystis aeruginosa and its mechanism - Linna Shao; Shi Huang; Liexiong Zhang; Yu Wu; Cai Cheng; Xiaoliang Guo; Jie Yu; Xingyu Xiang; Wenqi Zhang; Xuehan Xu; Lingzi Zuo; Lingling Feng (Algal Research, 2025)

Efficient removal and action mode of low-cost zinc-based metal-azolate frameworks regulated by ligand on Microcystis aeruginosa - Cai Cheng; Jie Yu; Linna Shao; Yu Wu; Shi Huang; Liexiong Zhang; Xuehan Xu; Xingyu Xiang; Xiaoliang Guo; Lingling Feng (Chemical Engineering Journal, 2025)

Efficient immobilization of CMlrA on mesoporous carriers for synchronized harmful Microcystis blooms suppression and microcystin degradation - Yu Wu; Linna Shao; Cai Cheng; Xianyong Kou; Shi Huang; Liexiong Zhang; Jie Yu; Xuehan Xu; Xingyu Xiang; Xiaoliang Guo; Lingling Feng (Journal of Hazardous Materials, 2025)

Pregnancy-induced changes in the toll-like receptor pathway in the ovine duodenum - Linna Gao; Haiquan Ding; Qianqian Shi; Xinxin Wang; Leying Zhang; Ling Yang (Veterinary Immunology and Immunopathology, 2025)

Corrigendum to ‘Heavy metals and metalloids exposure and liver function in Chinese adults - A nationally representative cross-sectional study’ [Environ. Res. 252-P2 (2024) 118653] - Shiyu Wang; Yuebin Lyu; Saisai Ji; Nankun Liu; Bing Wu; Feng Zhao; Zheng Li; Yingli Qu; Yuanduo Zhu; Linna Xie; Yawei Li; Zheng Zhang; et al. (Environmental Research, 2024)

Magnetic recyclable chitosan-graphene immobilized microcystinase A: Removal of microcystins from harmful microcystis blooms - Cai Cheng; Honglin Liu; Jie Yu; Shi Huang; Liexiong Zhang; Linna Shao; Xiaoliang Guo; Lingling Feng (Process Safety and Environmental Protection, 2024)

Dietary seafood as a potential modifier in the relationship between per- and polyfluoroalkyl substances (PFASs) burden and prediabetes/diabetes: Insights from a nationally representative cross-sectional study - Yingli Qu; Nan Sheng; Saisai Ji; Zheng Li; Jinghua Wang; Yitao Pan; Xiaojian Hu; Xulin Zheng; Yawei Li; Haocan Song; Linna Xie; Wenli Zhang; et al. (Journal of Hazardous Materials, 2024)

Heavy metals and metalloids exposure and liver function in Chinese adults — A nationally representative cross-sectional study - Shiyu Wang; Yuebin Lyu; Saisai Ji; Nankun Liu; Bing Wu; Feng Zhao; Zheng Li; Yingli Qu; Yuanduo Zhu; Linna Xie; Yawei Li; Zheng Zhang; et al. (Environmental Research, 2024)

Paleontology Knowledge Graph for Data-Driven Discovery - Yiying Deng; Sicun Song; Junxuan Fan; Mao Luo; Le Yao; Shaochun Dong; Yukun Shi; Linna Zhang; Yue Wang; Haipeng Xu; Huiqing Xu; Yingying Zhao; et al. (Journal of Earth Science, 2024)

Challenges to environmental governance arising from the Russo–Ukrainian conflict: Evidence from carbon emissions - Linna Han; Zixuan Zhou; Baofeng Shi; Yong Wang (Journal of Environmental Management, 2024)

Performance evaluation of resource-based city transformation: A case study of energy-enriched areas in Shaanxi, Gansu, and Ningxia - Qi Wen; Jie Fang; Linna Shi; Xinyan Wu; Anmeng Luo; Jinmei Ding (Journal of Geographical Sciences, 2023)

Mixed-linker MOFs-derived cross-linked copolymer electrolyte enables high lithium mobility for dendrite-free all-solid-state batteries - Jia Zhou; Xingfa Zeng; Linna Dong; Liya Chen; Xiangrong Wei; Yang liu; Liyi Shi; Le Yu; Jifang Fu (Chemical Engineering Journal, 2023)

Effects of water–nitrogen coupling on soil water and nitrogen, photosynthesis, yield and water use of lettuce under different application rates of poly‐γ‐glutamic acid - Lu Liu; Wenjuan Shi; Linna Pang (Irrigation and Drainage, 2023)
As an environmentally friendly, super water‐absorbable agent and fertilizer synergist, the influences of poly‐γ‐glutamic acid (γ‐PGA) on soil N and crop photosynthesis are still not well understood. A pot experiment was conducted to evaluate the effects of water–nitrogen coupling on soil water and nitrogen content, photosynthesis, yield and irrigation water use efficiency (IWUE) of lettuce under different γ‐PGA application rates. In this study, there were three factors and four levels: γ‐PGA with four application levels of 0, 1, 2 and 4 g kg −1 ; the rates of urea were 0, 0.2, 0.4 and 0.6 g kg −1 ; and the irrigation amounts were 40%, 60%, 80% and 100% of the lettuce water requirement (ET c ). The results showed that within 8 days after sowing, the soil water and nitrogen (NO 3 − ‐N and NH 4 + ‐N) content increased with increasing γ‐PGA application rates. The amount of irrigation water and nitrogen application had an effect on IWUE, net photosynthetic rate ( P n ) and stomatal conductance ( G s ). Lettuce yield was significantly correlated with P n , G s and intercellular CO 2 concentration ( C i ) by path analysis. Moreover, the P2N2W3 treatment (γ‐PGA 2 g kg −1 , nitrogen 0.2 g kg −1 and 80% ET c ) was the most suitable treatment to obtain the highest lettuce yield and IWUE.

The poverty evolution of typical countries along the Belt and Road and implications from China’s poverty reduction experiences - Linna Shi; Yongsheng Wang; Yansui Liu; Yuheng Li (Journal of Geographical Sciences, 2022)

Knowledge mapping analysis of research progress and frontiers in integrated disaster risk management in a changing climate - Lihong Wang; Zaiwu Gong; Linna Shi; Zewen Hu; Ashfaq Ahmad Shah (Natural Hazards, 2021)

Using magnetic susceptibility to evaluate pollution status of the sediment for a typical reservoir in northwestern China - Huiyun Pan; Xinwei Lu; Kai Lei; Dongqi Shi; Chunhui Ren; Linna Yang; Lijun Wang (Environmental Science and Pollution Research, 2019)

Optimization of wind-marine hybrid power system configuration based on genetic algorithm - Hongda Shi; Linna Li; Chenyu Zhao (Journal of Ocean University of China, 2017)

Combining multi-source data to explore a mechanism for the effects of micrometeorological elements on nutrient variations in paddy land water - Hezhen Lou; Shengtian Yang; Changsen Zhao; Zhiwei Wang; Xiaolin Liu; Liuhua Shi; Linna Wu; Fanghua Hao; Mingyong Cai (Paddy and Water Environment, 2017)

Suitable hepatitis B vaccine for adult immunization in China - Linna Yang; Jun Yao; Jing Li; Yongdi Chen; Zheng-gang Jiang; Jing-jing Ren; Kai-jin Xu; Bing Ruan; Shi-gui Yang; Bing Wang; Tian-sheng Xie; Qian Li (Immunologic Research, 2016)

Progresses on microwave remote sensing of land surface parameters - JianCheng Shi; Yang Du; JinYang Du; LingMei Jiang; LinNa Chai; KeBiao Mao; Peng Xu; WenJian Ni; Chuan Xiong; Qiang Liu; ChenZhou Liu; Peng Guo; et al. (Science China Earth Sciences, 2012)